2020
DOI: 10.1111/are.14872
|View full text |Cite
|
Sign up to set email alerts
|

A case study of biofilter activation and microbial nitrification in a marine recirculation aquaculture system for rearing Atlantic salmon (Salmo salarL.)

Abstract: Development of new technology within aquaculture the industry is important in order to expand seafood production or pursue cost-effective operations within fish farming. Today, recirculating aquaculture systems (RASs) are used for rearing salmon in countries such as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Cultures were initially identified by gram staining. Suspected cultures were evaluated for presence of ammonia and nitrite and vice versa for production of nitrite and nitrate (Saha et al 2014;Roalkvam et al 2020). Identification of Nitrosomonas was tested by the Nessler's reagent (Raud et al 2013;Agus Fitri et al 2017) and Nitrosomonas and Nitrobacter were confirmed through Trommsdrof's reagent (Hanks & Weintraub 1936;Kshatri et al 2017).…”
Section: Bacteriological Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures were initially identified by gram staining. Suspected cultures were evaluated for presence of ammonia and nitrite and vice versa for production of nitrite and nitrate (Saha et al 2014;Roalkvam et al 2020). Identification of Nitrosomonas was tested by the Nessler's reagent (Raud et al 2013;Agus Fitri et al 2017) and Nitrosomonas and Nitrobacter were confirmed through Trommsdrof's reagent (Hanks & Weintraub 1936;Kshatri et al 2017).…”
Section: Bacteriological Analysesmentioning
confidence: 99%
“…as probiotics were found to be significant in maintaining the water quality properties and in reducing the load of pathogenic bacteria (Sunitha & Krishna 2016). Nitrifying microbial community has the ability for better fish production by promoting water parameters (Roalkvam et al 2020;Xu et al 2020). Therefore, the application of probiotics could effectively decrease the contaminant levels in water bodies, reducing the load of pathogenic microbes and enhance survival of aquatic animals.…”
Section: Introductionmentioning
confidence: 99%
“…The slow development of nitrifying bacteria makes the biofilter less efficient during the activation period, causing reduced water quality due to increased concentrations of ammonia and nitrite, which can be harmful for the fish or inhibit further microbial biofilter development (Roalkvam et al, 2021). Several factors can impact the development of the microbial communities such as temperature and salinity of the biofilter, and this is an area of current research in RAS (Kinyage and Pedersen, 2016;Navada et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a relatively lower stocking density provides low, stable concentrations of ammonia, nitrite, and organic load. And it can promote the development of nitrifying bacterial populations in RAS bioreactors (Roalkvam et al, 2021). At the same time, the breeding density should not be too low, because the increase of living space will increase the energy consumption at low densities, which may lead to the decrease of feed utilization rate and reduced economic benefit.…”
Section: Effects Of Environmental Factors On Rasmentioning
confidence: 99%